Design of rapid first-aid alert systems for 2-wheeled vehicles via smartphones' inertial sensors. Issue 11 (2016) - Lucchetti, Alberto; Tanelli, Mara; Savaresi, Sergio M.; Santucci, Mario
Abstract: Road accidents involving two-wheeled vehicles are numerous indeed, and quite often cause the riders severe injuries. Therefore, developing automatic features that are able to detect the fall of the vehicle and autonomously issue first-aid calls is of particular interest for this type of vehicles. Such systems constitute a very interesting additional feature to be installed on new vehicles, even though vehicle-based solutions could hardly be cost-effective, as they would require additional sensors. To solve the problem in a low-cost and portable way, this paper proposes to use the GPS and the acceleration sensors that are on board of any modern smartphone. By properly processing these signals it is possible to detect whether the vehicle and/or the rider is lying on the ground and to issue an emergency call. The results are based on the analysis of experimental data measured on both an electric and a traditional two wheeled vehicle.